Penurunan Biaya Inventori di PT SEMB PEL Menggunakan Metode Vendor Managed Inventory - Sugianto, Yunita Kurniawati; Octavia, Tanti (Jurnal Titra, 2014)
In this work we applied Vendor Managed Inventory (VMI) for reducing raw material inventoriesâ cost in PT SEMB PEL. VMI is implemented for 40 of 6679 parts in this Final Project. The result shows the implementation of VMI can reduce actual lead time from 65% to 95%. This lead time reduction causes inventory cost reduction for 30 parts towards the target.